Silent night [videorecording (Blu-Ray)] - Griffin, Camille; Griffin, Camille; Knightley, Keira, 1985-; Goode, Matthew, 1978-; Griffin Davis, Roman, 2007- (RLJE Films, 2022)
A family hosts their annual Christmas dinner party for friends and family as an imminent catastrophe is about to destroy the world.